2020
DOI: 10.1002/cbf.3512
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA targeting of the non‐canonical planar cell polarity pathway in the developing neural tube

Abstract: MicroRNAs (miRNAs) provide context-dependent transcriptional regulation of genes comprising signalling networks throughout the developing organism including morphogenesis of the embryonic neural tube (NT). Using a high-sensitivity, high-coverage microarray analysis platform, miRNA expression in the murine embryonic NT during the critical stages of its formation was examined. Analysis of a number of differentially expressed (DE) miRNAs enabled identification of several gene targets associated with cellular proc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 70 publications
0
3
0
Order By: Relevance
“…The role of Wnt/PCP pathway in vertebrate cell movement during embryogenesis was first found in Xenopus and zebrafish (Heisenberg et al, 2000; Wallingford et al, 2000). During neurulation, when the neuraxis is elongated and eventually neural tube is closed, the convergent extension of the mid region of the neural plate occurs (Mukhopadhyay et al, 2020; Wallingford et al, 2020) which is mediated by PCP pathway. The core genes Frizzled ( Fzd ) and VANGL of PCP pathway encode transmembrane proteins (Nikolopoulou et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…The role of Wnt/PCP pathway in vertebrate cell movement during embryogenesis was first found in Xenopus and zebrafish (Heisenberg et al, 2000; Wallingford et al, 2000). During neurulation, when the neuraxis is elongated and eventually neural tube is closed, the convergent extension of the mid region of the neural plate occurs (Mukhopadhyay et al, 2020; Wallingford et al, 2020) which is mediated by PCP pathway. The core genes Frizzled ( Fzd ) and VANGL of PCP pathway encode transmembrane proteins (Nikolopoulou et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Precise control of NPC behaviors, such as proliferation, differentiation and survival, is essential for coordinating this process and preventing open neural tube defects (NTDs). miRNAs are ideal regulators for orchestrating these cellular behaviors for normal neural tube (NT) formation by binding to multiple targets that regulate the planar cell polarity pathway (70). A mouse development study demonstrated that miR-302/367 expression started in the embryonic region after implantation and became restricted to the anterior neural tube by embryonic day 8.5 (55).…”
Section: Roles Of Mir-367 In Disease Pathogenesismentioning
confidence: 99%
“…The nervous system is enriched in miRNAs, which play important roles in neural development [15][16][17][18]. The possible mechanism underlying the effectiveness of environmental risk factors in NTDs was recently explored via miRNA expression using low-or highdensity microarrays [19][20][21][22][23], including reports of the abnormal expression of miRNAs in NTDs. In particular, several studies have reported that miRNA expression dysregulation contributes to the mechanism of RA-induced NTDs [24,25].…”
Section: Introductionmentioning
confidence: 99%